Alcoholism and Sexual Dysfunction : Issues in Clinical Management. - Carruth, Bruce (Taylor and Francis, 2014)
Experts provide specific methodologies for clinicians working with recovering alcoholics and their families. This landmark study of sexual issues in alcoholism treatment addresses impotence in male alcoholics, the sexual dynamics of the client-counselor relationship, homosexual alcoholics, and many other important issues.